Information Literacy Skills and Computer Assisted Instruction - Wade, Linda L. (Valdosta State University, 2001)
The purpose of this study was to evaluate the effectiveness of an interactive multimedia tutorial followed by a classroom teacher- led practice session on student skill in and attitude toward one component of information literacy skills - locating and accessing information. The teacher's experiences and attitude in relation to this tutorial were also studied. This research was conducted using two average ability, ninth-grade language arts classes. The results of the study indicated that computer assisted instruction is an effective method of delivering information literacy skills instruction. Students were able to select an appropriate database for their topic and navigate through, select, and print information that supported their focus questions with minimal involvement on the part of the teacher. Since the tutorial/practice model proved to be effective, additional modules will be developed to support teacher- led information literacy instruction. This model more thoroughly integrates information literacy skills into the curriculum and solves the logistical problems of media specialists teaching all students.
Keywords: Interactive multimedia; Tutorial; Information literacy; teacher- led; Educational technology; Teaching--Aids and devices; Computer-assisted instruction